Chile : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This note discusses Chile's macroeconomic policy framework, the role of institutions in Chile, policies over time, export specialization and economic growth, trade policy strategy and recent agreements, an overview of recent developments in capital markets, and corporate financing in Chile. The role of the public sector in establishing debt benchmarks, an assessment of the country's external position, distress among Chile's foreign-owned firms, balance sheets of public sector finances, and an update on the Chilean banking system have been noted in this paper.